Evaluasi Program Penanggulangan Gizi Bagi Balita Gizi Kurang (WASTING) Di Puskesmas Oepoi Kota Kupang Tahun 2024 - Apriliany, Angelica Indry; Baumali, Alberth Matu Salak; Setia, Agustina; Boro, Regina Maria (Kupang Journal of Food and Nutrition Research, 2025)
Malnutrition (wasting) is a condition caused by starvation over a certain period of time and the presence of chronic diseases. Based on the Indonesian health survey (SKI 2023) The prevalence of malnutrition (wasting) based on BB/TB or BB/PB indicators in Indonesia in 2023 was 6.4%. The prevalence of malnutrition status (wasting) based on BB/PB or BB/TB indicators in toddlers in East Nusa Tenggara was 9.4% and the Kupang City area was 12.1%. Referring to information from the Service (2024), there were 909 cases of malnutrition recorded in the Oepoi Health Center working area during the period of January to December 2024. To find out the results of the Evaluation of the Nutrition Management Program for Malnutrition (wasting) Toddlers at the Oepoi Health Center in 2024. The type of research used was qualitative research using the CIPP method (Context, Input, Process and Product) with a descriptive design. This research was conducted in May 2025. The sampling technique used in this study was the Snowball sampling technique, which consisted of 14 respondents. The data collected included the planning, implementation, and results of the six programs that had been implemented at the Oepoi Community Health Center in 2024. The results showed that the nutrition education program, exclusive breastfeeding, complementary foods (MP-ASI), supplementary feeding (PMT), vitamin A, and deworming had been planned and implemented, but with various obstacles. The nutrition education program and exclusive breastfeeding had not reached optimal coverage, while the MP-ASI and PMT programs showed better results even though there were still problems with malnutrition among toddlers. Evaluation of the Nutrition Management Program for Malnourished Toddlers at the Oepoi Community Health Center in Kupang City in 2024 had been implemented in accordance with applicable procedures, but of the six programs evaluated, three of the six programs had not achieved maximum results